Worldwide Esophageal Cancer Collaboration: clinical staging data. Issue 7 (1st October 2016) - Rice, T. W.; Apperson-Hansen, C.; DiPaola, L. M.; Semple, M. E.; Lerut, T. E. M. R.; Orringer, M. B.; Chen, L.-Q.; Hofstetter, W. L.; Smithers, B. M.; Rusch, V. W.; Wijnhoven, B. P. L.; Chen, K. N.; et al.
Summary: To address uncertainty of whether clinical stage groupings (cTNM) for esophageal cancer share prognostic implications with pathologic groupings after esophagectomy alone (pTNM), we report data—simple descriptions of patient characteristics, cancer categories, and non–risk-adjusted survival—for clinically staged patients from the Worldwide Esophageal Cancer Collaboration (WECC). Thirty-three institutions from six continents submitted data using variables with standard definitions: demographics, comorbidities, clinical cancer categories, and all-cause mortality from first management decision. Of 22, 123 clinically staged patients, 8, 156 had squamous cell carcinoma, 13, 814 adenocarcinoma, 116 adenosquamous carcinoma, and 37 undifferentiated carcinoma. Patients were older (62 years) men (80%) with normal body mass index (18.5–25 mg/kg 2, 47%), little weight loss (2.4 ± 7.8 kg), 0-1 ECOG performance status (67%), and history of smoking (67%). Cancers were cT1 (12%), cT2 (22%), cT3 (56%), cN0 (44%), cM0 (95%), and cG2-G3 (89%); most involved the distal esophagus (73%). Non–risk-adjusted survival for squamous cell carcinoma was not distinctive for early cT or cN; for adenocarcinoma, it was distinctive for early versus advanced cT and for cN0 versus cN+. Patients with early cancers had worse survival and those with advanced cancers better survival than expected from equivalent pathologic categories based on prior WECC pathologic data. Thus, clinical and pathologic categories do not share prognostic implications. This makes clinically based treatment decisions difficult and pre-treatment prognostication inaccurate. These data will be the basis for the 8th edition cancer staging manuals following risk adjustment for patient characteristics, cancer categories, and treatment characteristics and should direct 9th edition data collection.